2010
DOI: 10.1159/000316134
|View full text |Cite
|
Sign up to set email alerts
|

Redundant Mechanisms for Vascular Growth Factors in Retinopathy of Prematurity in vitro

Abstract: Background: Current treatments for retinopathy of prematurity (ROP) targeting single vascular growth factors are ineffective in preventing neoangiogenesis. Methods: We investigated the redundant/compensatory mechanisms between vascular growth factors in ROP. Cultured retinal vascular endothelial cells under CoCl2-induced hypoxia were transfected with recombinant adeno-associated virus type 2-vascular endothelial growth factor (VEGF) or pGIPZ-VEGF RNA interference to up- and downregulate VEGF express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…[24][25][26][27][28] This hypothesis is directly supported by our observation that intravitreal injection of the VEGF-A antagonist bevacizumab strongly reduced the development of vascular tortuosity in the OIR model, consistent with a recent report by Rabinowitz et al, 29 and prevented dilation of veins as well as proliferation of endothelial cells. This model also suggests that plus disease should correlate with the level of VEGF produced during the hypoxic phase of ROP.…”
Section: Discussionsupporting
confidence: 88%
“…[24][25][26][27][28] This hypothesis is directly supported by our observation that intravitreal injection of the VEGF-A antagonist bevacizumab strongly reduced the development of vascular tortuosity in the OIR model, consistent with a recent report by Rabinowitz et al, 29 and prevented dilation of veins as well as proliferation of endothelial cells. This model also suggests that plus disease should correlate with the level of VEGF produced during the hypoxic phase of ROP.…”
Section: Discussionsupporting
confidence: 88%
“…Forooghian et al show significant increases of intraocular inflammatory cytokine secretions (such as Il-8 and TGF-β 2 ) in patients with proliferative diabetic retinopathy (PDR) following intravitreal injection of bevacizumab. Another report by Xiang et al 14 demonstrated an increased expression of angiopoietin1 and bFGF1 in retinal vascular endothelial cells in low-expressing VEGF groups in patients with retinopathy of prematurity. These studies support the notion that compensatory mechanisms may be at play following intraocular delivery of bevacizumab.…”
Section: Discussionmentioning
confidence: 90%
“…6,8,11,[35][36][37][38] Conditional knockout mice lacking ADAM17 in endothelial cells show decreased revascularization of the central avascular area 5 ; these results are therefore consistent with a model in which the lack of TIMP3 increases the activity of ADAM17, which in turn could increase revascularization, whereas injection of TIMP3 could prevent revascularization by blocking ADAM17. VEGF-A is highly upregulated in mouse OIR, [39][40][41] and previous studies have shown that VEGF-A/VEGFR2 signaling activates ADAM17 to promote crosstalk with the EGFR and stimulate migration of endothelial cells. 29,30 Since the injection of TIMP3 might also affect the binding of VEGF-A to the VEGFR2, 21 injection of TIMP3 could interfere with pathological neovascularization by inhibiting two crucial components of this pathway, binding of VEGF-A to the VEGFR2 and the activation of ADAM17.…”
Section: Discussionmentioning
confidence: 99%